The Immune Responses of DDY Mice infected S. aureus After Treatment of M. citrifolia Fruit Crude Extract - Mufidah, Zumrotul; Rifa’i, Muhaimin; Rahayu, Sri (Proceeding International Conference on Global Resource Conservation, 2013)
Infection disease that caused by bacteria is one of the illness in several developing countries including in Indonesia, with high mortality rate. One of the plants that can be used as medical herbal is Morinda citrifolia. The aim of this study is to know the immune response of mice with S. aureus infection by change to quantitativesâ lymphocytes and neutrophils after administration of M. citrifolia fruit crude extract. Mice were divided into two groups there are Non-Infection and infection. Non Infection is without S. aureus and than infection has S. aureus. The each groups are including control, dose 1 (25 mg/kg BW), dose 2 (100 mg/kg BW), and dose 3 (300 mg/kg BW). Oral treatment carried out for 20 days and injection of S. aureus at day 21 after with a concentration is 109 cell/ml. Relative number of neutrophil cell (Gr-1) and T cell subsets was measured using the BD FACSCaliburTM Flowcytometer. Data were analyzed using two way ANOVA (p<0.05). The result showed that administration of M. citrifolia crude extract was significantly changes in the relative amounts Gr-1+, CD4+, and CD8+ T cells. Â Keywords: immunomodulators, Morinda citrifolia, Staphylococcus aureus Â